ANALISIS PENGENDALIAN KUALITAS DENGAN METODE STATISTICAL PROCESS CONTROL PADA PRODUK SOLAR WATER HEATER - Rifkidananto, Ardhana; Surachman, Surachman (Jurnal Kewirausahaan dan Inovasi, 2022)
This study aims to determine the quality control of Solar Water Heater products at PT Wijaya Karya Industri Energi has been running optimally. This type of research is descriptive research. Data collection is done by using observation technique, while the data analysis method uses statistical process control. The results of the calculation of the percentage value of each sub group, the center line value (CL), the upper limit value (UCL), and the lower limit value (LCL) in the Solar Water Heater production process are within the control limits except for the A & B and C press fin processes. Based on the Damage Standard that has been set by PT Wijaya Karya Industri Energi, the damage during the research period did not exceed the Damage Standard limit, it shows that the quality control implemented by PT Wijaya Karya Industri Energi has been running optimally.